Isolated trochlear shear fracture of the distal humerus: a case report - Mistarihi, Saeb Mefleh; Azam, Ehab Hamzeh; Shari, Naser Fuad; Al Qasaimeh, Motaz Mohammad Ali; Hawasheh, Mohammad Jumah (International Journal of Research in Orthopaedics, 2022)
Laugier was the first to describe an isolated humeral trochlea fracture in 1853. We report the case of a patient with an isolated fracture of the trochlea and discuss the underlying mechanisms and the clinical, radiological features of this pathology and surgical management of this rare fracture. The elbow arthrotomy was done via an anteromedial approach, with the interval through the flexor-pronator muscles medially and the brachialis muscle laterally. The trochlea was temporally fixed by two Kirschner wires, and the definitive fixation was obtained by two cannulated. Herbert screws from anterior to posterior. The elbow was immobilized and splinted in a flexed position (70 degrees) for two weeks to allow soft tissue healing and minimize pain. After cast removal, rehabilitation of elbow was established and actively assisted mobilization for three months. The isolated trochlea fracture is a rare injury and usually, it is associated with other injuries such as elbow dislocation. Few studies in the literature described such fracture and the anteromedial approach; most of these studies described the use of a direct medial approach to the elbow. Several fixation methods were described in the literature, including k-wires, AO compression screws, and headless compression screws. Isolated fracture of the trochlea is rare. The mechanisms causing this fracture are complex; the usual mechanism of isolated trochlear fractures is falling on the palm with the elbow extended and supinated. In our report, the patient disclosed that he felt directly on his flexed elbow. Trochlear fractures require open reduction and internal fixation to achieve anatomical reduction, with excision of the small osteochondral fragments that may be complicated by arthritic changes.